Tracer Study: Studi Rekam Jejak dan Tingkat Kepuasan Pengguna Terhadap Lulusan Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Curup - Siti Zulaiha; Tika Meldina; Chandra Dio Saputra; Yuli Tri Astuti (AR-RIAYAH : Jurnal Pendidikan Dasar, 2021)
The aims of this study are to determine: 1) the acceptance numbers of graduates for job opportunities, 2) the waiting period for graduates to get a job, 3) the relevance of the graduates’ qualification to the field of work, and 4) the level of stakeholders’ satisfaction with graduates of the PGMI (Education of Basic School Teachers) study program of IAIN (The Institute for Islamic Studies) Curup. This research method was survey research with quantitative descriptive data analysis. The data collection was carried out using questionnaires sent directly via email, social media, face to face and by telephone. The research results showed that: 1) the graduates of PGMI Study Program of IAIN Curup were well accepted in job opportunities, 2) the waiting period for graduates to get a job was in the range of 0 - 3 months after graduation, 3) there was relevance of graduates’ work field to their qualification, 4) the level of stakeholders’ satisfaction with graduates of the PGMI Study Program of IAIN Curup was in very good criteria. Based on the results of the study, it was suggested that institutions need to carry out tracer study activities in a sustainable manner so that they can find out the condition of graduates after completing their education in the institutions. Then, feedback was expected from alumni and stakeholders to get a higher response rate. In addition, the results of this study can be a consideration for stakeholders at universities to develop curriculum so that they can improve the competence of graduates in accordance with the demands of the work field.